Pola Komunikasi Remaja pada Keluarga Pesisir - Mahastuti, Dewi; Fitriani, Adwitya Alvinur; Sinay, Jeanith Tesalonika Ivana; Putri, Bilqis Aprisha; Jalasenastriska, Clarisa (Program Studi Psikologi Islam (IAIN) Kediri, 2023)
Communication is one of the daily activities that are often carried out by humans. Every aspect of human life is influenced by communication. The smallest human unit to carry out a communication that starts from the family. Communication in the family which is the way family members interact with family members, where good communication can be created between parents and children. The purpose of this study was to determine the communication patterns of adolescents in the family, with their parents. This research is devoted to young coastal families who live on the coast of Kenjeran Beach, Surabaya. The subjects in this study were adolescents aged 13-18 years who lived in the area around the coast of Kenjeran, Surabaya, East Java, totaling 33 people. Collecting data using a Likert Scale questionnaire with 25 items. The results of the study showed that the dominant communication pattern was the monopoly pattern with a percentage of 54.55%.